Motherhood and Terrorism: Understanding Female Involvement through Typologies in Indonesia - Leebarty Taskarina,; Adrianus Eliasta Meliala,; Ni Made Martini Putri,; Laila Indriyanti Fitria, (Technium Social Sciences Journal, 2025)
The phenomenon of female terrorism is a new field of study that challenges traditional understandings that often associate women with their compassionate attitudes and maternal roles. Through a feminist and risk assessment perspective, this research investigates the typology of motherhood-based female terrorism, focusing on the manifestation of maternal values and their intersection with extremist ideologies. This study used qualitative analysis of primary and secondary data sources, including interviews with 20 female perpetrators of terrorism, focus group discussions with 15 experts in the field of terrorism, and analysis of scholarly literature. This study underscores the existence of women's agency and semi-autonomy in terrorism activities based on the preceding experiences of oppression, victimization, manipulation, and mystification. The character and value of motherhood of female terrorists depend on social and cultural practices throughout the subject's life. Based on the experiences of these informants, this study identifies seven typologies of motherhood-based female terrorism, namely (1) Lone of Motherhood, (2) Underage Motherhood, (3) Paramilitary Motherhood; (4) Entrepreneur Motherhood, (5) Academia Motherhood, (6) Migrant Motherhood; (7) Domestic Motherhood. In conclusion, this study offers critical insights into the typology of motherhood-based female terrorism and provides a foundation for future research and policy development aimed at addressing the complexities of female participation in extremist activities.